Internal Sources of Labour Productivity Growth in Russia - E. V. Balatsky; N. A. Ekimova (Мир новой экономики)
In this article, the authors analysed the readiness of Russian regions for the integration of technological innovations. In this context, managerial dichotomy “borrowing/creation of innovations” is of fundamental importance. The right choice of the way to increase productivity in the regions of the country represents a nontrivial task since the wrong solution would lead to significant economic losses. The authors proposed to use the concept of technological boundary to increase objectivity managerial decisions making. “Technological boundary” means the relative productivity of the region corresponding to the average productivity in the United States, the excess of which allows the region to develop new production technologies. The use of the concept of technological frontier and comparison of labour productivity in the Russian regions showed that only two regions in the country could act as drivers for the development of their own new technologies. At the same time, the available data and calculations show that in many regions there are leading companies of different industries with extremely high productivity and ability to act as innovative local drivers within the regions. This circumstance made it possible to formulate a multi-step strategy to accelerate the technological diffusion for Russia.